Normative study and evaluation of age influence on Brainstem auditory evoked potentials in mixed breed dogs] - Palumbo, M. I P [UNESP]; Resende, L. A L [UNESP]; Borges, A. S. [UNESP] (FapUNIFESP (SciELO), 2013)
The aim of this paper was to obtain normative data of auditory evoked potentials from 34 mixed breed dogs and evaluate the age influence. The animals were divided in two groups of different ages and auditory evoked potential was performed with a 85dB stimulus intensity. Group 1 included 16 dogs between 1 and 8 years of age, and group 2 included 18 dogs with over 8 years of age. The length and head diameter were measured and there was no statistical difference between the two groups. In group 1, mean latencies of waves I, III, and V were 1.13; 2.64, and 3.45ms, and the intervals I-III, III-V, and I-V were 1.51; 0.81, and 2.32 ms, respectively. In group 2, the mean latencies of waves I, III and V were 1.15, 2.62, and 3.55ms, and the intervals I-III, III-V, and I-V were 1.47, 0.93, and 2.40ms, respectively. The latencies observed in this study were similar to previous studies conducted by other authors. It was observed that significant differences were present for wave V and intervals III-V and I-V latencies when comparing groups with different ages, consequently this characteristic must be considered during BAEP result interpretation.
Keywords: Age; Auditory evoked potentials; Dogs; Hearing